Traditional crafts in digital commerce: Consumer value and behavior on TikTok China’s ceramic live-streaming - Limin, Fang; Abidin, Shahriman Zainal; Harun, Zahirah; Xiumian, Chen (Edelweiss Applied Science and Technology, 2025)
This paper analyzes how TikTok China’s live-streaming platform transforms the marketing of Jingdezhen ceramics. Using Structural Equation Modeling (SEM), the research examines how consumers’ perceived value influences their purchase satisfaction and subsequent behavior during Jingdezhen ceramics live-streaming sessions. The model identifies and quantifies key influence pathways, revealing that perceived enjoyment during live-streaming is a crucial mediating variable affecting consumers’ perceived value and purchase satisfaction of Jingdezhen ceramics. The study validates the significant impact of integrating Jingdezhen ceramics’ traditional cultural characteristics with live-streaming presentation methods on consumer purchase decisions through rigorous SEM analysis. The statistical modeling reveals causal relationships among ceramic value perception, live-streaming interaction experience, and purchase outcomes. While the research is limited to Jingdezhen ceramic products, this SEM-based approach provides empirical evidence for optimizing traditional ceramic product marketing on digital platforms while offering theoretical guidance and practical implications for Jingdezhen ceramics’ inheritance and innovation in the digital era.